2013
DOI: 10.1177/1533317513494440
|View full text |Cite
|
Sign up to set email alerts
|

Daily Assistance for Individuals With Dementia via Videophone

Abstract: We previously developed remote reminiscence conversation and schedule prompter systems via the videophone to improve psychological stability and to assist individuals with dementia to perform household tasks. Our results showed that the psychological stability of 1 patient persisted for 3 hours after remote conversations. The task completion rate afforded by the schedule prompter system, which displays a video reminder series automatically, was 52%. In the present study, we also investigated whether psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Both parties can indicate regions of interest, and the therapist or caretaker can control the visual effects that accompany the reminiscence videos. Evaluations of this system have found that most individuals find remote RT enjoyable, and some have had persisting benefits in terms of managing behavioral symptoms, such as anxiety, irritability, and restlessness (Kuwahara, Yasuda, Tetsutani, & Morimoto, 2010; Yasuda, Kuwahara, Kuwabara, Morimoto, & Tetsutani, 2013; Yasuda, Kuwahara, & Morimoto, 2009). While remote RT could reduce barriers due to transportation difficulties, they may create new barriers for individuals lacking technical expertise or necessary hardware.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both parties can indicate regions of interest, and the therapist or caretaker can control the visual effects that accompany the reminiscence videos. Evaluations of this system have found that most individuals find remote RT enjoyable, and some have had persisting benefits in terms of managing behavioral symptoms, such as anxiety, irritability, and restlessness (Kuwahara, Yasuda, Tetsutani, & Morimoto, 2010; Yasuda, Kuwahara, Kuwabara, Morimoto, & Tetsutani, 2013; Yasuda, Kuwahara, & Morimoto, 2009). While remote RT could reduce barriers due to transportation difficulties, they may create new barriers for individuals lacking technical expertise or necessary hardware.…”
Section: Resultsmentioning
confidence: 99%
“…While remote RT could reduce barriers due to transportation difficulties, they may create new barriers for individuals lacking technical expertise or necessary hardware. The researchers involved in networked reminiscence therapy addressed this concern by setting up the system in the participants’ homes and remotely starting applications (Yasuda et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Results show that more mixed methods work is needed to flesh out the "friendly guide" persona suggested in this paper. Future versions of the ICA should also integrate multimodal prompts using voice and video or haptic feedback as and when appropriate [39,40]. …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there are approaches that promote the use of assistive technology to help people with dementia with activities of daily living (ADLs) [20,13,18,8] and support different kinds of therapy to address psychological, emotional and behavioral symptoms of dementia [1,3,14,15].…”
Section: Related Workmentioning
confidence: 99%
“…Yasuda et al [20] developed a remote reminiscence conversation and schedule prompter system via videophone to improve psychological stability and to assist individuals with dementia to perform household tasks. They observed that psychological stability of 1 patient persisted for 3 hours after remote conversations.…”
Section: Related Workmentioning
confidence: 99%